2007
DOI: 10.1086/522109
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries and Outflows in the Circumstellar Dust of Mira A

Abstract: Asymmetries and motions in the dust shell surrounding Mira A (o Ceti) are reported. Measurements were taken with the UC Berkeley Infrared Spatial Interferometer (ISI), a three-element interferometer operating at 11.15 m. At the time of these observations, it was in a linear, east-west configuration with a maximum baseline of 12 m and thus had a resolution of better than 100 mas. Three years of data (2003)(2004)(2005) are presented and permit observation of the movement of dust shells over time. Fits are made t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…Lopez et al (1997) found a best fit to observations in the IR taken with the Infrared Spatial Interferometer (ISI) by models with inhomogeneities or clumps. Chandler et al (2007) presented a number of explanations for their ISI observations, among them shock waves and non-uniform dust formation. Recently, Stewart et al (2016b) produced images of Mira by analyzing occultations by the rings of Saturn observed with the Cassini spacecraft showing layers and asymmetries in the stellar atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Lopez et al (1997) found a best fit to observations in the IR taken with the Infrared Spatial Interferometer (ISI) by models with inhomogeneities or clumps. Chandler et al (2007) presented a number of explanations for their ISI observations, among them shock waves and non-uniform dust formation. Recently, Stewart et al (2016b) produced images of Mira by analyzing occultations by the rings of Saturn observed with the Cassini spacecraft showing layers and asymmetries in the stellar atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Interferometry and high angular resolution imagining are also becoming important for studying both the structure and the dynamics of AGB star atmospheres, giving new insights into the shock propagation and dust condensation distances (see e.g. Chandler et al 2007;Karovicova et al 2013;Ohnaka et al 2012Ohnaka et al , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the elevation of a few percent of each of the mass of each of these "puffs" of material over each pulsation cycle, on average, could support the observed Mira mass loss rate. Chandler et al (2007) reported their detection of episodic mass loss around Mira at 11.15 µm with the ISI interferometer. Our detection in H band is compatible with their finding.…”
Section: Discussionmentioning
confidence: 99%